Change in Exhaled Volatile Organic Compounds (VOC) Profile and Interleukin-17 Serum in Lung Cancer Patient - Agil Dananjaya; Ungky Agus Setyawan; Susanthy Djajalaksana; Arinto Yudi Ponco Wardoyo (Perhimpunan Dokter Paru Indonesia (PDPI)/The Indonesian Society of Respirology (ISR), 2023)
Background: In recent years, there have been studies regarding biomarkers for early detection of lung cancer. The expansion of tumor is accompanied by distinct metabolic process product, which results in identifiable changes in the volatile organic compounds (VOC) emission profile. The content of such molecules differs between healthy and lung cancer patients. Furthermore, the expression of Interleukin-17 (IL-17) was linked to the clinical and pathological aspects of lung cancer patients. The aim of this study is to profile the exhaled VOC and the level of IL-17 in the serum of lung cancer patient.Methods: Fourty patients with confirmed lung cancer and 42 healthy subjects as control were gathered for this study. VOC was measured using breath analyzer and sensor array, while IL-17 was measured by ELISA. Statistical analysis was conducted using Kruskal-Wallis test and Spearman correlation test with P<0.05 considered significant.Results: We examined 15 VOCs and found that ethanol (C2H5OH), formaldehyde (CH2O), toluene (C7H8) and ammonia (NH3) in lung cancer patient were increased significantly compared to control (P<0.05; P<0.05; P<0.05 and P=0.001 respectively). However, the level of IL-17 in control subjects was higher (P=0.299) than patients with lung cancer. Conclusion: Ethanol, formaldehyde, toluene and ammonia can potentially be used as biomarkers for lung cancer. However, the role of IL-17 in lung cancer screening still needs further investigations.